Sitagliptin Augments Protective Effects of GLP-1 against Advanced Glycation End Product Receptor Axis in Endothelial Cells - Ishibashi, Y.; Matsui, T.; Takeuchi, M.; Yamagishi, S. (Hormone and Metabolic Research, 2011)
Sitagliptin is a stable inhibitor of dipeptidyl peptidase-IV, a responsible enzyme that mainly inactivates glucagon-like peptide-1 (GLP-1), and now one of the widely used agents for the treatment of diabetes. However, effects of sitagliptin on vascular injury are largely unknown. Since advanced glycation end products (AGEs) and their receptor (RAGE) axis contribute to vascular damage in diabetes, we investigated here whether sitagliptin inhibits the AGE-RAGE-induced endothelial cell damage in vitro. Although effects of 10 pM GLP-1 or 0.5 μM sitagliptin monotherapy on RAGE gene and protein expression were modest, combination therapy completely blocked the AGE-induced increase in RAGE mRNA and protein levels in human umbilical vein endothelial cells (HUVEC). AGEs induced reactive oxygen species (ROS) generation and reduced endothelial nitric oxide synthase (eNOS) mRNA level in HUVEC, both of which were also completely blocked by the treatment with 10 pM GLP-1 and 0.5 μM sitagliptin, but not with GLP-1 or sitagliptin monotherapy. Further, anti-RAGE antibody restored the decrease in eNOS mRNA level in AGE-exposed HUVEC. The present study suggests that sitagliptin augments the effects of GLP-1 on eNOS mRNA level in AGE-exposed HUVEC by suppressing RAGE expression and subsequent ROS generation. Sitagliptin may work as a vasoprotecitve agent in diabetes by blocking the AGE-RAGE axis.